Green synthesis, characterizations of silver nanoparticles using sumac (Rhus coriaria L.) plant extract and their antimicrobial and DNA damage protective effects - Gur, Tuğba (Frontiers in Chemistry, 2022)
Today, antimicrobial resistance against bacteria has become an important global public health problem. In this sense, the development of new biomedical solutions is becoming increasingly important. Especially plant-based nanoparticles produced by green synthesis are used in many fields. AgNPs have an important place in nanoscience and nanotechnology, especially in nanomedicine. Therefore, the present study was conducted to synthesize AgNPs using the medicinal plant extract sumac and to characterize them using advanced techniques and to determine the antibacterial activity of some bacteria that cause disease. Nanoparticles produced by green synthesis are used in a wide area around the world due to their many advantages such as environmentally friendly, economically and non-toxically. In this study, AgNPs were biosynthesized using sumac extract and evaluated for their antibacterial potency against Bacillus cereus, Bacillus subtilis, Enterococcus faecalis, Pseudomonas aeruginos, and Candida albicans. UV-Vis spectroscopy of the prepared sumac-mediated silver solution showed the absorption maximum at about 400 nm. According to the TEM results obtained, it was observed that the particles were spherical, approximately 4 nm in size, and showed a homogeneous distribution. The sizes of nanoparticles formed by XRD pattern were supported and silver nanoparticles were obtained. According to the obtained XRD results, the crystal nature of nanoparticles in face-centered cubic structure was confirmed by the peaks in the XRD model corresponding to the planes (111) (200) (220) and (311). It was observed that the synthesized AgNPs provided a strong protection against plasmid DNA damage. It was determined that the inhibition zone diameters of biosynthesized nanoparticles measured in terms of antibacterial activity were between 10 and 14 mm. As a result, the study revealed significant antibacterial activity of the synthesized AgNPs due to extensive membrane damage.